Está en la página 1de 11

Outline Solutions to Problems in Matrix Algebra

MSc Quantitative Techniques

1 Given

D =

7

5

2

4

,

E =

2

4

,

F = 3

7

1(a) Determine for each of the following whether the products DE,ED and DF are defined. If so, indicate the dimensions of the product matrix.

Here D is 2 × 2, E is 2 × 1 and F is 1 × 2.

DE is of dimension 2 × 1, FD is of dimension 1 × 2, EF is of dimension 2 × 2, FE is of dimension 1 × 1. The following are not defined: ED and DF.

The following are defined:

1(b) Calculate EF and FE.

EF =

2

4

3

FE = 3

7

7

=

6

12

2

4 = 34

14

28

1(c) Calculate (DE)F and D(EF).

(DE)F= D(EF) = 66 78

1

154

182

2 Given matrices A and B

A = 4 2

9

1

B = 2 1

4

7

2(a) Calculate AB and demonstrate that the commutative law of multipli- cation does not hold under matrix multiplication.

AB

=

4 × 2 + 9 × 1

2 × 2 + 1 × 1

BA =

2 × 4 + 4 × 2

1 × 4 + 7 × 2

Clearly AB

= BA.

4 × 4 + 9 × 7 2 × 4 + 1 × 7

2 × 9 + 4 × 1 1 × 9 + 7 × 1

= 17

5

= 16

18

79

15

22

16

2(b) Calculate the determinant of A.

The determinant of A is

|A| = 4 · 1 2 · 9 = 4 18 = 14

2(c) Find the inverse of matrix A.

There are many legitimate ways of finding the inverse. Here is one.

We know that A 1 A = I, the identity matrix, so

9

1

Multiplying out on the LHS, we get

a

c

d b 4

2

=

1

0

0

1

4a + 2b

=

1

9a + b

=

0

4c + 2d

=

0

9c + d

=

1

These are two pairs of equations in four unknowns, and we can solve for the unknown a, b, c and d manually. The solution is

A 1 = 1

14

1

7

2

9

14

2 7

3 Consider the equation system

4x 1 + 6x 2 + 8x 3

=

2

(1)

x 1 + x 2 + x 3

=

1

(2)

4x 1 + 3x 2 + 2x 3

=

1

(3)

3(a) Write the system in matrix notation, as Ax=b.

To write the equation system as Ax=b, we have

A =

4

1

4

6

1

3

8

1

2

x =

x

x

x

1

2

3

2

b = 1

1

3(b) How many solutions does this system have? Find them.

None, as simple manipulation of the equations shows the equations to be inconsistent. To see why, note subtract equation (3) from equation (1) to get

3x 2 + 6x 3 = 1

Multiply equation (2) by 4 and subtract equation (3) to get

x 2 + 2x 3 = 3

These two relations are inconsistent.

3

4 Consider

1

A = 0

0

1

1

0

1

1

1

4(a) Compute A (the transpose of A).

4(b) Compute AA

A =

1

1

1

0

1

1

AA = 2

3

2

1 1

2

0

0

1

1

1

1

4(c) Find the inverse A 1 . Going through the usual steps, you should get

1

A 1 = 0

0

4

1

1

0

0

1

1

5 Given

2

B = 1

+1

1

1

2

3

β

1

For what value(s) of β is B not invertible?

|B| = 2

1

2

β

1

1

1

+1

β

1

+ 3

1

+1

2 1 = 0

|B| = 2(1 2β) 1(1 β) + 3(2 1) = 0

|B| = 2 + 4β + 1 + β 9 = 0 =β = 2

5

6 A macroeconomic model is specified by the following relations

Relation A:

Y

= C + I

= 100 + 0.7Y

C

  = 180 125r

I

Relation B: M D =

M

¯

M S = 255

D = 220 + 0.2Y 175r

Find equilibrium Y and r using Cramer’ s Rule.

The variables of interest are Y and r, so we begin by simplifying both relations purely for these two variables.

Relation A

Y = 100 + 0.7Y + 180 125r

Y (1 0.7) + 125r = 280

0.3Y + 125r = 280

Relation B

220 + 0.2Y 175r = 255

0.2Y 175r = 35

Writing these in matrix notation,

0.3

0.2

+125

175 r

Y

=

280

35

|A| = 52.50 25 = 77.50

Y =

280

35

+125

175

77.5

= 49000 4375

77.5

= 688.71

r =

0.3

0.2

280

35

77.5

= 10.5 56

77.5

= 0.59

6

7 Let

3

A = 0

0

8

4

3

1

3

4

Find the characteristic roots and characteristic vectors.

8

4 λ

3

We require values for λ such that |A λI | = 0.

That is, expanding down first column of [A λI],

[A λI] =

3 λ

0

0

1

3

4 λ

|A λI| = (3 λ)

4 λ

3

3

4 λ

0

8

3

1

4 λ

+ 0

8

4 λ

1

3

=

= (3 λ)(4 λ)(4 λ) 9(3 λ) = 0

Rewriting the characteristic equation as

= (3 λ)[(4 λ)(4 λ) 9] = 0

Solutions:

i) (3 λ) = 0 =λ 1 = 3

ii) (4 λ)(4 λ) 9 = 0 =λ 2 8λ + 7 = 0 =λ 2 = 7, λ 3 = 1

Then λ 1 = 3, λ 2 = 7, λ 3 = 1 are the eigenvalues.

For some eigenvalue λ i , we have, for i = 1, 2, 3

[A λ i I]x i = 0

where x i is the eigenvector corresponding to λ i .

Consider the case where λ 2 = 7 . Here

7

[A λ 2 I] =

3 λ 2

0

0

8

4 λ 2

3

1

3

4 λ 2

=

4

0

0

8

3

3

1

3

3

Clearly x 2 must satisfy the equation

4

0

0

8

3

3

1

3

3

x

x

x

21

22

23

=

0

0

0

Note that Rank [A λ 2 I ] is 2. In fact, the 3rd row, multiplied by 1, is identical to the 2rd row.

Solving the system

4x 21 + 8x 22 + x 23 = 0 =⇒ −4x 21 + 9x 22 = 0 =x 21 = 3x 22 + 3x 23 = 0 =x 22 = x 23 3x 22 3x 23 = 0 =x 22 = x 23

9 4 x 22

Since we can choose x 22 arbitrarily, choose to eliminate fraction, yield- ing

x 2 =

9

4

4


, with x 22 = x 23 = 4

We can check that our value of x 2 is indeed an eigenvector correspond- ing to the eigenvalue λ 2 = 7, by showing that Ax 2 = λ 2 x 2

Ax 2 =

3

0

0

8

4

3

1

3

4

9

4

4

=

63

28

28

9

= 7 4

4

= λ 2 x 2

Similarly we can find that for λ 1 = 3, x 1 = 1 0 vector (determined only up to a scalar multiple).

Analogously, for λ 3 = 1, x 3 = 7 2 2

Verify that the trace of the matrix equals the sum of the characteristic roots.

0 is an eigen-

8

The trace is the sum of the diagonal elements, so equals 3+4+4 = 11. The sum of the characteristic roots is 1+3+7 = 11.

Verify that the determinant of the matrix equals the product of the characteristic roots.

Expanding using the first column, the determinant equals 3 · (16 9) = 21. The product of the characteristic roots is 1 · 3 · 7 = 21.

9

8

Show that if λ is an eigenvalue of a square matrix A, then λ 2 is an

eigenvalue of A 2 .

If λ is an eigenvalue of A, then

Ax = λx

where A is a square matrix, λ is a scalar and a x

vector. Pre-multiplying both sides by A

= 0 is an (n × 1)

AAx = Aλx.

But note that the right hand side is the same λAx and since we know that Ax = λx, we can write

AAx = λAx = λλx

A 2 x = λ 2 x

If so, λ 2 is an eigenvalue of A 2 .

10

9 Given a 2 × 4 matrix X , define P = X(X X) 1 X and

Show that P is idempotent.

PP = X(X X) 1 X

But (X X)(X X) 1 = I, so

X(X X) 1 X

PP = X(X X) 1 X = P

Show that M is idempotent.

MM = [I-P][I-P]

or

M 2 = I P P + P 2

M=I-P.

But as we know that P is idempotent, so P 2 = P. The result follows. Show that MP=0

pr

MP = [I-P]P

MP = P P 2

But as we know that P is idempotent, so P 2 = P. The result follows.

11